Predicting wood stiffness of lodgepole pine trees using acoustic tools and green density - James D. Stewart; Ross Koppenaal; Antoine Lalumière; Roger J. Whitehead (The Forestry Chronicle)
Upstream identification of wood properties using non-destructive testing methods such as acoustic velocity (AV) measurements is important for optimizing allocation of wood to mills or products. We evaluated the effectiveness of field AV measurement tools in predicting lodgepole pine wood stiffness (modulus of elasticity, MOE) as measured by Silviscan on wood samples. AV was measured on trees and logs from six sites in Alberta and British Columbia. We evaluated the effect on MOE estimation of calculating averages of the adjustment factor k and of green density (GD) at different spatial scales from individual tree to population. The effect of using forest inventory variables on MOE prediction were also examined. Prediction of tree-level MOE from tree-level measurements of AV, k and GD resulted in R2 values of 0.59. Using estimates of k and GD averaged at plot, site or population scales significantly diminished the R2 of the MOE predictions at tree level. Predicting MOE at plot or stand level from corresponding averages of AV, k and GD gave R2 values >0.8. Including inventory variables in tree-level MOE predictions increased the R2 to 0.62. AV measurements can give operationally useful estimates of MOE in lodgepole pine trees at the stand level.